A direct injection liquid chromatography tandem mass spectrometry method for the kinetic study on iodinated contrast media (ICMs) removal in natural water. (March 2020) - Lopez-Prieto, Israel J.; Wu, Shimin; Ji, Weikang; Daniels, Kevin D.; Snyder, Shane A.
Abstract: Iodinated contrast media (ICMs) are a class of X-ray contrast media worldwide utilized for radiographic procedures. Since they cannot be removed efficiently during water treatment, they can be found in surface and groundwater. In this work, a rapid and sensitive direct injection liquid chromatography-tandem (LC-MS/MS) method for the simultaneous analysis of seven ICMs media (iopamidol, ioxitalamic acid, diatrizoic acid, iothalamic acid, iohexol, iomeprol and iopromide) in complex aqueous matrices has been developed and validated. The MDLs for the analytes ranged from 0.7 to 21 ng L −1 in ultrapure water, and recoveries ranged from 86 to 100% in drinking water, 85–103% in groundwater and 84–105% in WWTP effluent. A stereo-isomer for iopromide was separated. This analytic method was applied to investigate the removal of target ICMs by low pressure ultra violet light (LPUV) advanced oxidation processes with three oxidants, hydrogen peroxide, free chlorine and monochloramine in groundwater. Results showed that the addition of oxidants did not enhance attenuation of ICMs, since fluence-based decay apparent rate constants were similar (KUV = 3.2 × 10 −3, KUV-Cl2 = 3.6 × 10 −3 and KUV-NH2 = 3.4 × 10 −3 10 −3 cm 2 mJ −1 ). This yielded direct photolysis is the main mechanism to attenuate target ICMs. Graphical abstract: Image 10028 Highlights: Rapid and sensitive direct injection method for analysis of seven target ICMs. The method was validated in complex aqueous matrices such as secondary effluent, groundwater and drinking water. Removal of seven target ICMs by LPUV/H2 O2, LPUV/Cl2 and LPUV/NH2 Cl.